THE CHALLENGES OF PRE-SERVICE ENGLISH LANGUAGE TEACHERS: A REFLECTION OF THEIR TEACHING PRACTICUM - Priajana, Nana (STIT Buntet Pesantren Cirebon, 2022)
This research was conducted to explore some of the probable issues encountered by pre-service English teachers when conducting teaching practicum (PPL) activities at schools. The research focuses on (1) how do the practitioners practice their language skills (English) and pedagogical competencies to teach at schools while conducting their teaching practicum? (2) what obstacles or challenges do they encounter during PPL at schools? The researcher employed questionnaires and interviews involving PPL practitioners, teachers and field supervisors to explore the problems faced by the practitioners. The research findings reveal that there are several potential obstacles encountered by practitioners while conducting PPL at schools. The interesting Issues revealed problems accentuating the teaching planning process, pre-teaching activities, core activities and post-teaching activities. The results of this study are indeed valuable for pre-service English teachers as evaluative paces to improve their teaching competencies and English language skills in carrying out PPL activities at schools to be professional English teachers.